Operations Management of Multipurpose Cooperatives in Rinconada Area, Philippines - Tarin, Joecile G. (The Indonesian Institute of Science and Technology Research, 2024)
This study was conducted to determine the compliance of 13 multipurpose cooperatives in Rinconada with Memorandum Circular No. 2013-15 Series 2013 from the Cooperative Development Authority. It identified respondent profiles in terms of operational years, memberships, personnel, asset size, and services offered. The extent of compliance was assessed across organizational, social, economic, and financial aspects. Difficulties faced by cooperatives were determined, along with the relationship between profiles and compliance. Universal and convenience sampling methods were employed to select 119 respondents, including cooperative management, staff, and committee members. Data collection utilized questionnaires, interviews, and checklist observations. Results indicated that organizational factors minimally impacted operations, except for services offered. Social aspects showed associations but lacked statistical significance. Economically, asset size and services offered significantly influenced operations. Financially, factors like operational years, members, personnel, asset size, and services offered significantly shaped operational practices. The study suggests the development of a manual of operation to enhance cooperative effectiveness.